(untitled) (Global Journal of Management and Business Research, 2023)
State and international migratory routes toward the state of Yucatan have expanded exponentially, due to its well-known level of social welfare within Mexican territory. The study of quiet, peaceful environments, appropriate for human development, quite underestimated in the industrialized era, has been insufficient. This state has produced a significant proportion of mass, national, and international migrant populations looking for permanent settlement in other places. Therefore, this study was done during the 2019-2020 school year among secondary students immersed in the migratory phenomenon. The geopolitical and social contexts of origins are analyzed to determine their degree of influence on the possible causal variables of social constructions. It also looks at the imaginaries of migrant students and the multifaceted, volatile behaviors that may lead to ethical dilemmas, caused by audaciousness, among the majority of indigenous adolescents. For this study, we used a non-probabilistic sample at several school divisions, as well as the observation of participants through the application of the focus survey technique and content analysis.